S-phase – an independent prognostic marker in upper tract urothelial carcinoma. (2nd November 2022) - Malm, Camilla; Jaremko, Georg; Brehmer, Marianne
Abstract: Objectives: To evaluate S-phase fraction as a predictor of invasiveness and cancer-specific survival in upper tract urothelial carcinoma (UTUC). Patients and methods: One hundred and fifteen patients having undergone radical nephroureterectomy were analysed with histology in radical nephroureterectomy specimens as reference test and S-phase fraction as index test. Ploidy and S-phase were determined using flow cytometry. Differences in S-phase fraction were calculated between stages, grades (WHO 1999 and 2004 classifications), ploidy and patients that died of UTUC and those who did not. Five- and 10-year-cancer-specific survivals were calculated. Areas under the ROC curve (AUCs) of S-phase fraction in relation to tumour stage and to death from UTUC were measured. Multiple Cox regression was performed. Results: Independent prognostic markers of death from UTUC were S-phase fraction and stage. Correlation between S-phase fraction and risk of dying from UTUC was strong, with a 17% greater risk of death from UTUC with every 1% increase in S-phase fraction, hazard ratio = 1.17, 95% CI = 1.10–1.25, p  < 0.001, Spearman's rho ρ  = 0.65. AUCs for S-phase fraction as predictors of stage and death from UTUC were 0.8 (95% CI = 0.705–0.894) and 0.77 (95% CI = 0.67–0.87), respectively. Cancer-specific survival was statistically significantly different between stages, ploidy and WHO 1999 grades, but not between WHO 2004 grades. This was also reflected in S-phase fraction, which differed in LG-G1 compared with LG-G2 and in HG-G2 compared with HG-G3. Conclusion: S-phase fraction was a good test for predicting both invasiveness and cancer-specific survival. Using both WHO 1999 and 2004 classifications, rather than one system alone, had a higher predictive value of cancer-specific survival.